Full Run-2 boosted right-handed heavy neutrino and single leptoquark searchin ATLAS - Davou, Christopher Lawrence (My University, 2021)
Two searches for physics beyond the Standard Model scenario are presented in this thesis, the first is a search for right-handed gauge boson WR, decaying into a boosted right-handed heavy neutrino NR, and a lepton while the second search is the single leptoquark search decaying to a lepton and a quark using 139 fb−1of proton- proton data from the ATLAS detector at √s=13 TeV. Only the electron final state is considered in this thesis for the right-handed gauge boson search which uses a large-radius jet containing an electron as a proxy for the NR. A detailed study to improve the identification of electrons close to jets in the context of this search is also presented. The result for the search shows no significant deviation from the Standard Model implying no new physics was observed. The single leptoquark search presented in this thesis considers leptoquarks decaying into an electron or muon in association with a strange or bottom quark in the final state. The leptoquark mass range is between 500 GeV - 2500 GeV. For each of the signal regions, the expected upper limits at 95% CL on the single leptoquark production cross section as a function of the leptoquark mass were set for leptoquarks coupling to electron, muon, strange and bottom quarks. In the electron b-veto channel, the model exclude leptoquarks coupling to strange quarks at masses below 1.1 TeV while for leptoquarks coupling to b-quarks and electrons, the model excludes the masses below 1.0TeV. Similarly, for the muon channel, the exclusion is at masses below 1.1 TeV for the leptoquarks coupling to strange quark and 1.0 TeV for the leptoquarks coupling to the bottom quark. No new physics has been observed in this analysis
A thesis submitted in conformity with the requirements for the degree of Doctor of Philosophy, School of Physics, Institute for Collider Particle Physics, University of the Witwatersrand, 2021